Enhancing Student Learning Methods Through the KKNI Curriculum in the Islamic Economic Law Program at the Faculty of Sharia and Law UIN SU Medan - Tarigan, Tetty Marlina; Zahara, Fatimah (Jurnal Penelitian Medan Agama, 2024)
To enhance the qualifications of university graduates in Indonesia, the government issued Law No. 12 of 2012 on Higher Education and Presidential Regulation No. 8 of 2015 on the Indonesian National Qualifications Framework (KKNI). The KKNI curriculum serves as a guideline to align and integrate education, work training, and work experience with the job structure across various sectors. UIN SU organized a workshop in 2017 to reformulate a transdisciplinary curriculum based on KKNI to support its implementation. This study aims to examine the development of learning design through the KKNI curriculum in the Islamic Economic Law (Muamalah) Study Program at the Faculty of Sharia and Law, UIN SU Medan. Using a descriptive-analytical method, the study explores the learning design development process between lecturers and students and its impact on alumni. This qualitative research also discusses the implementation mechanisms of the KKNI-based learning design. The findings reveal that the development of the KKNI-based learning design has been implemented fairly well. However, additional intensive training for lecturers is necessary to enhance their understanding and application of the curriculum. This effort aims to make students more productive in actualizing their potential during the learning process. With the optimization of the KKNI curriculum, graduates of the Islamic Economic Law Study Program are expected to compete effectively in the workforce, meeting national competency standards.